Overview of soil conservation technologies and their perception by farmers in Nigeria - Junge, B.; Deji, O.F.; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl; Kirchhof, G. (Australian Centre for International Agricultural Research, 2009)
In Nigeria, West Africa, soil degradation has been one of the most critical environmental problems for along time. Hence, there has been and still is an urgent need to develop effective soil resource managementsystems that can reverse the trend. Sustaining soil productivity will enhance food security and alleviatepoverty. An extensive literature search that started in 2006 has shown that soil conservation has a longtradition, and earlier and present initiatives have resulted in various on-farm and off-farmtechnologies. Asthese have rarely been evaluated to establish adoption rates, an assessment study was performed in 2007 toanalyse the effectiveness and adoption of past and present soil conservation initiatives. Villages withdifferent types of conservation technologies were visited and farmers in south-west Nigeria wereinterviewed to obtain information on their experiences. Mulching, cover cropping and contour tillage arelikely to be effective on-farm soil conservation measures practised in Nigeria. They are generally adoptedby farmers as they are compatible with the existing farming system, and cheap and easy to install andmaintain. Education, knowledge on soil conservation, labour availability and membership in organisationshave a positive influence on the adoption rate of technologies.